Improving the Operating Condition of a Thermoelectric System for Achieving High Temperature Difference in Indoor Heating - Behzad-, M (Springer Science and Business Media Deutschland GmbH, 2023)
Thermal comfort in the buildings is provided by different type of heating, ventilation, and air conditioning systems (HVAC). Several efforts have been made for localized heating and cooling. Application of thermoelectric systems in space heating and cooling is among the recent solutions. Yet, the efforts were mainly remained in laboratory level. This work aims to optimize a thermoelectric system performance for localized heating application in order to achieve higher temperature difference with the environment. The application of the system was optimized through a new control scheme of the fan that is on/off operation instead of continuous functioning. This feature not only increased the temperature outlet of the device but also enhanced the coefficient of performance up to 11%. The new configuration facilitates the application of thermoelectric systems in building sector especially in localized space heating considering individual thermal comfort level. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.